An update on the treatment of pediatric-onset Langerhans cell histiocytosis through pharmacotherapy. (11th February 2018) - Minkov, Milen
ABSTRACT: Introduction : Langerhans cell histiocytosis (LCH) is a rare myeloid neoplasia driven by activation mutations alongside the MAPK pathway. Its broad spectrum of clinical manifestations and diverse course and clinical outcome, make interpretation of trial data difficult. Use of different stratification systems further complicates comparison among trials. Areas covered : This review summarizes the published data derived from prospective clinical trials from Phase II onwards. PubMed was searched using combinations of the keywords 'Langerhans cell histiocytosis', 'histiocytosis X', 'pediatric', 'children', 'treatment', and 'therapy'. Only full-length papers published in English and German were included in the review. Expert opinion : Mortality in multisystem LCH is restricted to patients with involvement of risk organs (hematopoiesis, liver and spleen) at diagnosis, and is particularly high (up to 60–70%) if systemic therapy fails to control the disease. For the rest of the cohort, mortality is almost negligible, and the main challenges are disease relapses and related permanent consequences (encountered in up to 50% of the survivors). While systemic therapy has clearly improved survival of patients with most severe disease form, its role in providing sustained disease control and preventing permanent consequences in patients with 'low risk' disease is less clear.